Cognitive and emotional factors associated with the desire to cease non-suicidal self-injury - Gray, Nicole; Hasking, Penelope; Boyes, Mark (WILEY, 2022)
Background: Due to cognitive and emotional differences between individuals who have and have not stopped self-injuring, we explored these in the context of desire to stop. Method: Australian university students (n = 374) completed cognitive and emotional measures. Comparisons were made between those who had self-injured in the past 12 months and those who had not, and between individuals who reported wanting to stop self-injuring and those who did not. Results: Approximately 20% of participants did not want to stop self-injuring. Cognitive emotional factors (psychological distress, self-efficacy to resist, difficulties regulating emotion, interpersonal functions, and outcome expectancies) differentiated individuals who had and had not stopped, but could not explain differences in desire to stop. Conclusion: Factors associated with desire to stop are not the same as factors underlying behavioural cessation. Motivational approaches to changes in self-injurious behaviour would be beneficial for clinicians and their clients.